Linking metabolites in eight bioactive forage species to their in vitro methane reduction potential across several cultivars and harvests - Verma Supriya; Wolffram Siegfried; Salminen Juha-Pekka; Hasler Mario; Susenbeth Andreas; Blank Ralf; Taube Friedhelm; Kluß Christof; Malisch Carsten Stefan (NATURE PORTFOLIO, 2022)
An in vitro Hohenheim gas test was conducted to analyze the fermentation end-products from 17 cultivars of eight polyphenol containing forage species. The polyphenol composition and proanthocyanidin (PA) structural features of all the cultivars were analyzed with UPLC-MS/MS in leaves of vegetative or generative plants. The samples were incubated with and without polyethylene glycol (PEG, a tannin-binding agent) to separate the tannin-effect on methane (CH4, ml/200 mg DM) production from that of forage quality. Sulla and big trefoil, two particularly PA rich species, were found to have the highest CH4 reduction potential of up to 47% when compared to the samples without PEG. However, concomitant reduction in gas production (GP, ml/200 mg DM) of up to 44% was also observed. An increase in both GP and CH4 production under PEG treatments, confirms the role of tannins in CH4 reduction. Moreover, PA structural features and concentration were found to be an important source of variation for CH4 production from PA containing species. Despite having low polyphenol concentrations, chicory and plantain were found to reduce CH4 production without reducing GP. Additionally, interspecies variability was found to be higher than intraspecies variability, and these results were consistent across growth stages, indicating the findings' representativeness.